The Effect of Game Style Training on the Speed and Accuracy of Jumping In Advance Basketball Players - Sabbah, Mohannad; Mohmmed, Sherzad (Journal of Physical Education, 2020)
The research aim at identifying the effect of game style training on developing speed and accuracy of double and triple points jump from different positions. The researchers designed two new tests for measuring speed and accuracy of (2 – 3) points jumping from different positions. They used the experimental method in (60) basketball players of the season 2019 - 2020 selecting (12) players from each of the following clubs (Al Adamia, Al Kehrbaa, Al Ketoot, Al Shorta, Al Nefot). The training program was followed then the data was collected and treated using proper statistical operations to conclude positive effect of game style training on developing speed and accuracy of jumping (2 – 3) points in favor of experimental method. The researchers recommended using this research results for game style training for developing speed and accuracy of (2 – 3) points jumping.